Enhanced fluorescence quantum yield of syndiotactic side-chain TPE polymers via Rh-catalyzed carbene polymerization: influence of the substitution density and spacer length. Issue 13 (6th March 2019) - Li, Xiao; Sun, Yuhao; Chen, Jian; Wu, Zhongying; Cheng, Pin; Li, Qian; Fang, Jianglin; Chen, Dongzhong
Abstract : The fluorescence quantum yields of the TPE-based C1 polymers also increase with the shortened spacer lengths and further improve by about 20% as compared with the corresponding C2 polyacrylate counterparts. Abstract : A series of syndiotactic C1 polymers P m TPE with tetraphenylethene (TPE) side groups attached through various length alkyl spacers of carbon numbers m = 2–6, 8, 10, and 12 have been prepared via Rh-catalyzed carbene polymerization, with the homologues with very short spacers encountering quite arduous challenges. All the polymers investigated possess typical aggregation-induced emission (AIE) properties whether in solution aggregates or in solid films and reveal a remarkable increase in fluorescence quantum yields with shortened alkyl spacer lengths, coinciding with the increased glass transition temperatures and in agreement with the same tendency to increase manifested by the TPE-based side-chain C2 polyacrylate polymers. Moreover, they display high fluorescence quantum yields with about 20% increase compared to their usual C2 polymer counterparts with the same side-chain spacer lengths. Their high quantum yields are unaffected by adequate thermal annealing, and they are thermodynamically stable as confirmed by the X-ray scattering analysis, indicating an unaltered highly constrained structure, thus significantly promoting the restriction of intramolecular rotations (RIR) of TPE luminogens and blocking the non-radiative channels. A testing paper strip coated with representative P4TPE is exemplified as an economical, reusable, and visualized method for TNT explosive detection with high sensitivity. The significant fluorescence emission enhancement of C1 polymers because of the high substitution density and syndiotactic regularity may provide an inspiring route for the preparation of further upgraded AIE polymer materials for various applications.